2009
DOI: 10.1091/mbc.e09-01-0021
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaGoLoco-Protein Pins Is a Target of Gαo-mediated G Protein–coupled Receptor Signaling

Abstract: Drosophila G␣ o . We identify Pins GoLoco domain 1 as necessary and sufficient for this unusual interaction with G␣ o -GTP. We further pinpoint a lysine residue located centrally in this domain as necessary for the interaction. Our studies thus identify Drosophila Pins as a target of G␣ o -mediated GPCR receptor signaling, e.g., in the context of the nervous system development, where G␣ o acts downstream from Frizzled and redundantly with G␣ i to control the asymmetry of cell divisions. INTRODUCTIONTrimeric G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 73 publications
(120 reference statements)
4
78
0
Order By: Relevance
“…However, the mechanisms controlling the interactions between GPR-containing proteins and their G-protein partners remain poorly understood. Such signals may involve coordinated positioning of GPR proteins within the cell, receptor-activated signaling cascades, regulatory proteins binding to non-GPR domains of the proteins, and/or non-receptor guanine nucleotide exchange factors acting on a GPR⅐G␣ i complex (2,3,(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…However, the mechanisms controlling the interactions between GPR-containing proteins and their G-protein partners remain poorly understood. Such signals may involve coordinated positioning of GPR proteins within the cell, receptor-activated signaling cascades, regulatory proteins binding to non-GPR domains of the proteins, and/or non-receptor guanine nucleotide exchange factors acting on a GPR⅐G␣ i complex (2,3,(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Previous in vitro studies of the interactions between Gα i/o proteins and AGS3 family proteins were consistent with either the AGS3 protein inactivating Gα signaling by acting as a guanine nucleotide dissociation inhibitor, or activating signaling by either Gα or Gβγ (Natochin et al, 2000; Bernard et al, 2001; Kopein and Katanaev, 2009). Our work clearly shows that AGS-3 acts upstream of Gα o to activate signaling via the Gα subunit.…”
Section: Discussionmentioning
confidence: 63%
“…We found that full-length GST-AGS-3 bound to only Gα o -GDP, the inactive state of the G protein, while the C-terminal fragment of AGS-3 containing the four GPR domains could additionally bind Gα o -GTP, the activated state. Thus, the Gα binding activity of full-length AGS-3 is similar to that of mammalian AGS3 and LGN and Drosophila Pins (Mochizuki et al, 1996; Takesono et al, 1999; Schaefer et al, 2000; Bernard et al, 2001; Kopein and Katanaev, 2009). The C-terminal GPR fragment of Pins also has the Gα-GTP binding activity we saw for the GPR fragment of AGS-3 (Kopein and Katanaev, 2009).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations